2022
DOI: 10.13189/saj.2022.100219
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Game Play Ability in a High School Sport Education Basketball Season

Abstract: To date, there is limited research investigating physical activity levels during a sport education season in high school physical education settings and how these are affected by ability levels. The aim of this study was to investigate (1) how students' game play in basketball would improve during a sport education season as a function of ability level, and (2) how students' MVPA levels differ as a function of game play ability. One class with 21 high school students (aged 16-18) participated in a 14-day sport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Physical education lesson; an increase in the percentage of MVPA is observed when it is carried out in outdoor games based on a physical activity away from monotony and when it is carried out with activities that require team play and cooperationoriented activities (Hartatiti et al, 2018;Wang and Zhou, 2022). When the physical education course is conducted by these criteria, students obtain MVPA degrees greater than 50% in swimming (Cardon et al, 2004), football (Harvey et al, 2016), basketball (Iserbyt et al, 2022), and handball units (Dania et al, 2017). In the research, MVPA was found to be greater than 50% for castled dodgeball game, which is one of the traditional children's games based on team and competition.…”
Section: Physical Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Physical education lesson; an increase in the percentage of MVPA is observed when it is carried out in outdoor games based on a physical activity away from monotony and when it is carried out with activities that require team play and cooperationoriented activities (Hartatiti et al, 2018;Wang and Zhou, 2022). When the physical education course is conducted by these criteria, students obtain MVPA degrees greater than 50% in swimming (Cardon et al, 2004), football (Harvey et al, 2016), basketball (Iserbyt et al, 2022), and handball units (Dania et al, 2017). In the research, MVPA was found to be greater than 50% for castled dodgeball game, which is one of the traditional children's games based on team and competition.…”
Section: Physical Activitymentioning
confidence: 99%
“…Researching the relationship between physical activity and performance in low economic income communities, Cohen et al, (2014) concluded that the time spent by the students in MVPA was sufficient and those movements requiring object control were positively related to displacement. Iserbyt et al, (2022), who investigated the relationship between MVPA and game performance according to skill levels, observed that students with high skills spent more time in MVPA. Skill level has played an important role in maintaining physical activity effectively.…”
Section: The Relationship Between Physical Activity and Game Performancementioning
confidence: 99%
See 3 more Smart Citations